Accessibility Requirements for External Environment, Internal Environment, Building Accessibility and Emergency Egress Specifically for PWDs - Baig, Lubaina Dawood; Ajmal, Sadaf; Khan, Muhammad Karamatullah (sourcecoder, 2025)
The current study aims to determine if government organizations in two Baluchistan cities were constructed in accordance with the approved building accessibility code, 2006, given the dearth of research on building accessibility for persons with disabilities (PWDs). A significant percentage of the population is made up of people with impairments, which hinders their ability to move around and utilize their surroundings. Until these people are able to move around and use their surroundings, full participation and equality cannot be attained. The current study is objective and is based on positivism approach. Data for this quantitative study, data was gathered using physical observation chechlist from 53 government organizations. The data was collected between July 2024–March 2025. Data analysis was done using Excel software. People with disabilities (PWDs) can access only 31% of government organizations overall. Approximately two-thirds of public institutions are inaccessible to people with disabilities due to inadequate infrastructure and services. Funding for projects pertaining to accessibility should be increased by the federal and provincial governments. Additionally, teaching key institutions on universal design principles is crucial for successful implementation of accessibility code. The current study aims to determine if government organizations in two Baluchistan cities were constructed in accordance with the approved building accessibility code, 2006, given the dearth of research on building accessibility for persons with disabilities (PWDs). A significant percentage of the population is made up of people with impairments, which hinders their ability to move around and utilize their surroundings. Until these people are able to move around and use their surroundings, full participation and equality cannot be attained. The current study is objective and is based on positivism approach. Data for this quantitative study, data was gathered using physical observation chechlist from 53 government organizations. The data was collected between July 2024–March 2025. Data analysis was done using Excel software. People with disabilities (PWDs) can access only 31% of government organizations overall. Approximately two-thirds of public institutions are inaccessible to people with disabilities due to inadequate infrastructure and services. Funding for projects pertaining to accessibility should be increased by the federal and provincial governments. Additionally, teaching key institutions on universal design principles is crucial for successful implementation of accessibility code.